Glutamine metabolism and ammonia death: targeted modulation for enhanced cancer immunotherapy - Du, Fei; Xiao, Linlin; Guojun, Wang; Dai, Qian; Li, Junxin; Zhao, Xin; Zhang, Qimin; Yang, Lan; Liu, Yujie; Hu, Yidan; Wen, Bo; Zhou, Jingqiu; et al. (Frontiers in Immunology, 2025)
Immunotherapy has rapidly emerged as a transformative advancement in cancer treatment, becoming essential for managing diverse malignancies. Despite the remarkable clinical efficacy of immunotherapies, including immune checkpoint inhibitors (ICIs) and chimeric antigen receptor (CAR)-T cells, across various tumor types, patient responses remain heterogeneous, with some tumors developing resistance through immune evasion strategies. Presently, the investigation of cell death mechanisms is gaining momentum as a promising avenue for immunotherapy optimization. Recent studies underscore that integrating cell death pathways with immunotherapy can significantly amplify anti-tumor immune responses. Ammonia, a metabolic byproduct within the tumor microenvironment (TME), has garnered increasing interest. Specifically, emerging research suggests that ammonia, accumulating in effector T cells as a result of glutamine metabolism, induces cell death. This distinct form of cell death, termed “ammonia death,” diverges from previously characterized mechanisms. This review examines the metabolic role of glutamine in various TME cells, explores the potential regulatory links between glutamine metabolism and ammonia-induced cell death, and evaluates the feasibility of targeting ammonia-induced cell death to enhance anti-tumor immunity and improve immunotherapy outcomes.